Aid for Trade-Harnessing Globalization for Economic Development. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Aid for trade can support countries trying to further benefit from the expanding global market place by helping to address poorly performing infrastructure and institutions. Needless to say, good policies also matter: trade liberalization, improving incentives for private investment in trade, and reducing the costs and improving the quality of services. Market access also matters; accordingly, a successful conclusion to the Doha Round remains a top policy objective. The paper highlights three challenges and suggests some areas for further consideration/action: making competitiveness a pillar of country growth strategies; filling the remaining gaps in trade-related assistance; and expanding the overall aid envelope and making full use of opportunity to replenish the International Development Association.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet